2022
DOI: 10.1371/journal.pone.0265616
|View full text |Cite
|
Sign up to set email alerts
|

Measurement instruments for parental stress in the postpartum period: A scoping review

Abstract: Background Parenting stress is a particular type of stress that is conceptualized as a negative psychological response to the numerous obligations associated with raising children. Despite a considerable increase in research on parenting stress, little attention has been given to the ways parenting stress are measured. Objectives This scoping review aimed to provide an overview of available instruments measuring parental stress and to describe their psychometric properties. Methods We conducted a scoping r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…This lack of evidence on the accuracy of postpartum stress instruments makes it challenging to understand and mitigate information bias related to postpartum stress. 27 Many studies have investigated the change trends of perinatal depression and anxiety symptoms in women after delivery. In a Canadian perinatal cohort study, anxiety and depression symptoms were found to be heterogeneous; this finding highlighted the importance of conducting multiple mental health assessments during the perinatal period.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of evidence on the accuracy of postpartum stress instruments makes it challenging to understand and mitigate information bias related to postpartum stress. 27 Many studies have investigated the change trends of perinatal depression and anxiety symptoms in women after delivery. In a Canadian perinatal cohort study, anxiety and depression symptoms were found to be heterogeneous; this finding highlighted the importance of conducting multiple mental health assessments during the perinatal period.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Moreover, postpartum stress is difficult to quantify, and data for the most effective postpartum stress instrument are limited. This lack of evidence on the accuracy of postpartum stress instruments makes it challenging to understand and mitigate information bias related to postpartum stress 27…”
Section: Introductionmentioning
confidence: 99%
“… 51 For example, Danielsen et al 52 found that the psychometric properties of adapted versions validated with different tests, recommended the inclusion of a quantitative validation phase that includes one or more tests focused on content validity, criterion validity, reliability and construct validity. Additionally, in a scoping review of Øygarden et al 53 on measurement instruments for parental stress during the postpartum period, it was reported that none of the 15 instruments contained information on measurement error, responsiveness, and interpretability. Echevarría-Guanilo et al 54 argue that researchers should have a comprehensive knowledge of psychometric properties to tailor the research design to the most appropriate psychometric properties of the instrument of interest.…”
Section: Introductionmentioning
confidence: 99%